1993
DOI: 10.1002/ptr.2650070720
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effect of Toki‐Shakuyaku‐San (TJ‐23) on hypoglycaemia/hypoxia‐induced neuronal damage in rat striatal slices

Abstract: The effect of Toki-Shakuyaku-San (TJ-23) was examined on various models of brain damage in uitro. TJ-23 (10 mg/mL) significantly protected striatal slices from dysfunction induced by high K + and BAY K-8644 but not from that by L-glutamate and N-methyl-D-aspartate, an effect which was similar to that of nifedipine, a CazC antagonist. The present findings, therefore, raised the possibility that TJ-23 expressed a neuroprotective action on hypoxidischaemia-induced brain damage by inhibiting an excess Ca2+ entry t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…reported to display neuroprotective effects on hypoglycemia/hypoxia-induced neuronal damage in in vitro rat brain slice (Kataoka et al, 1991). Furthermore, TSS has been reported to protect against glutamate-induced neuronal damage in cultured cerebellar granule cells (Watanabe et al, 1995).…”
mentioning
confidence: 96%
“…reported to display neuroprotective effects on hypoglycemia/hypoxia-induced neuronal damage in in vitro rat brain slice (Kataoka et al, 1991). Furthermore, TSS has been reported to protect against glutamate-induced neuronal damage in cultured cerebellar granule cells (Watanabe et al, 1995).…”
mentioning
confidence: 96%
“…This suggests that TJ-23 may have a neuroprotective effect for neuron death. Kataoka et al (1991) supported this hypothesis and demonstrated that application of TJ-23 to a neural cell suspension in a hypoglycaemic/hypoxic environment prolonged the survival time of the neurons, and further, TJ-23 treated neurons were able to synthesise and release dopamine even though neurons were suspended in a hypoglycaemic/hypoxic environment.…”
Section: Neuroprotective Effect For Neuron Death In the Brainmentioning
confidence: 61%
“…However, Oyama (1991) using microdialysis techniques reported no release of dopamine after administration of TJ-23 even though administered TJ-23 increased the concen-tration of dopamine in the cerebral cortex. Kataoka et al (1991) reported that administered TJ-23 acted on neural cell suspension directly and stimulated the synthesis and release of dopamine.…”
Section: Facilitatory Effect On Acetylcholine Receptor Activity In Thmentioning
confidence: 99%